Konflik dalam Pemilihan Umum Bupati dan Wakil Bupati Kabupaten Kotawaringin Barat Tahun 2010-2012 - Nugraha, Angga Aditya; Sardini, Nur Hidayat; Adulrahman, Wachid (Journal of Politic and Government Studies, 2017)
The election is important instrument in establishing the democracy, for general election and election in indonesian has been executed with principle luber and jurdil. Nevertheless, the success of the would not rule out reality that they are breaking the, cheating, and conflicts that have occurred. The conflict in the election in district west kotawaringin is an example of a conflict election inIndonesian. The conflict between candidates and society. Research objectives is reconstruction conflicts that have occurred in the field into the form of scientific work with explain the dynamics of conflict and the factors that for conflict election. Methods used in research this is the method qualitative descriptive with the collection primary and secondary data. Informants selected socialite is a political role in conflict and the community of district west kotawaringin and the support by candidates.The results show that the conflict in election in district west kotawaringin prolonged. Steps precondition conflict, practices money politics, election day, a lawsuit to the constitutional court, the actors play, tensions decisions by constitutional court and burning facilities the government. Conflict caused by decision electoral commission, the award constitutional court and the inauguration in central.Recommendations that may be given constitutional court decision better do a re-election and decisions ministries in the country better involving local government and appoint regent and vice-regent in district west kotawaringin and involving local communities.Keyword: Conflict, election, communityÂ